Answer:
6.47 x 10^-2
Step-by-step explanation:
this formula, doesn't rely on a product, relies on a "sum", or is namely an arithmetic sequence, aₙ₋₁ -3 is another way of saying, the value of the previous term minus 3, so it relies on the ordinal value of a term, so is an recursive formula, well, let's get it when n = 4.
Answer:
558
Step-by-step explanation:
|266 + 292|
=> | 558 |
=> 558
Move all terms to one side
4w^2 + 49 + 28w = 0
Rewrite 4w^2 + 49 + 28w in the form a^2 + 2ab + b^2, where a = 2w and b = 7
(2w)^2 + 2(2w)(7) + 7^2 = 0
Use the Square of Sum: (a + b)^2 = a^2 + 2ab + b^2
(2w + 7)^2 = 0
Take the square root of both sides
3w + 7 = 0
Subtract 7 from both sides
2w = -7
Divide both sides by 2
<u>w = -7/2</u>
Answer:
240 seventh graders passed
Step-by-step explanation:
300 x 0.8 = 240